Cellular endo‐lysosomal dysfunction in the pathogenesis of non‐alcoholic fatty liver disease. (15th December 2019) - Du, Jiang; Ji, Yu; Qiao, Liang; Liu, Yanli; Lin, Juntang
Abstract: Non‐alcoholic fatty liver disease (NAFLD), an increasingly devastating human disorder, is characterized by intrahepatic fat accumulation. Although important progress has been made in understanding NAFLD, the fundamental mechanisms involved in the pathogenesis of NAFLD have not been fully explained. The endo‐lysosomal trafficking network is central to lipid metabolism, protein degradation and signal transduction, which are involved in a variety of diseases. In recent years, many genes and pathways in the endo‐lysosomal trafficking network and involved in lysosomal biogenesis have been associated with the development and progression of NAFLD. Mutations of these genes and impaired signalling lead to dysfunction in multiple steps of the endo‐lysosomal network (endocytic trafficking, membrane fusion and lysosomal degradation), resulting in the accumulation of pathogenic proteins. In this review, we will focus on how alterations in these genes and pathways affect endo‐lysosomal trafficking as well as the pathophysiology of NAFLD.